The Discrepancy of Colonoscopical and Histopathological Findings in Infectious Colitis: Focus on Amebic Colitis - Salius Silih; Marcellus Simadibrata; Murdani Abdullah; Abdul Aziz Rani; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Result of colonoscopic examination in infectious colitis was varying. The aim of this study was to recognize the correlation between colonoscopical and histopathological findings in patients with infectious colitis at Cipto Mangunkusumo hospital, Jakarta. Method: A cross-sectional study had been conducted. There were 227 patients with infectious colitis with unidentified etiology and 17 patients with amebic colitis. In both groups, several variables had been studied including sex, age group and indication of colonoscopy by using Chi-square test. The relationship between hematochezia and amebic colitis event was also studied by using Chi-square test. To recognize the ability of colonoscopy test in diagnosing amebic colitis, we conducted diagnostic test by searching the sensitivity and specificity. Result: In both groups of infectious colitis, we found male more frequent than female. There was a significant difference mean of age in both group of infectious colitis (p = 0.04). The mean age of amebic colitis group was younger (35.86 ± 14.36 years) than the other infectious colitis group (45.34 ± 15. 90 years). The incidence of amebic colitis was more frequent in hematochezia than in non -hematochezia (p 0.001). The sensitivity and specificity of colonoscopy in diagnosing amebic colitis were 35% and 97%, respectively. Conclusion: There was a tendency of developing amebic colitis in patients with hematochezia than non-hematochezia. In diagnosing the presence of amebic colitis, colo noscopy examination has lo w sensitivity and high specificity. Keywords: discrepancy, infectious colitis, amebic colitis, colonoscopy, histopathological finding